Relationship between Body Anthropometric Measurement and Parathyroid Hormone in Female Subjects - Mabruratussania Maherdika; Meita Hendrianingtyas (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
The distribution of fat tissue is related to the risk of metabolic diseases. Parathyroid Hormone (PTH) is an essential hormone for calcium homeostasis. According to several types of research, body fat affects PTH levels. Currently, Body Mass Index (BMI) is not the only parameter needed to identify the body fat distribution in accordance with chronic disease risks such as Waist Circumference (WC), Waist to Hip Ratio (WHR), and Waist to Height Ratio (WHtR). The study aimed to determine the relationship between body anthropometric measurement and PTH. A cross-sectional study was performed on a healthy population of 75 healthy female volunteers with a BMI â‰¥ 23 kg/m2. Waist circumference, WHR, WHtR, and BMI measurements were carried out and followed by the PTH fragment 1-84 (PTH1-84) test. Data were analyzed using the Spearman test with a significance of p<005. There was no significant correlation between PTH and WHR (r=0.057; p=0.628). There was weak correlation between PTH and BMI (r=0.268; p=0.020), WC (r=0.287; p=0.012) and WHtR (r=0.238; p=0.04). Body mass index, WC, and WHtR can be used as anthropometric parameters to determine PTH disorders